Retrospective diagnosis of congenital cytomegalovirus infection in children with autism spectrum disorder but no other major neurologic deficit - Sakamoto, Ayako; Moriuchi, Hiroyuki; Matsuzaki, Junko; Motoyama, Kazunori; Moriuchi, Masako (Brain & development (Tokyo. 1979), 2015)
Aim: Congenital cytomegalovirus (CMV) infection can cause a variety of neurological deficits of delayed onset in infants who are asymptomatic at birth. The aim of this study was to investigate the prevalence of congenital CMV infection among children with autism spectrum disorder (ASD) in Nagasaki, Japan. Methods: Twenty-nine children with ASD who were born in Nagasaki and had no other major neurological deficits were recruited. Two of the patients were excluded due to significant perinatal events. The remaining 27 children were investigated retrospectively for congenital CMV infection by analyzing dried blood spot samples or dried umbilical cords for CMV DNA using real-time PCR. Results: CMV DNA was detected in two (7.4%) of the 27 children. Neither of the patients had perinatal histories suggestive of congenital CMV disease or other neurological deficits, including hearing impairment and epilepsy. The severity of their autistic disorders varied considerably. Conclusions: The rate of congenital CMV infection in this study (two of 27 children with ASD), which was significantly (p=0.004) higher than the incidence of congenital CMV infection in Nagasaki (0.31%, 10/3230 live births), suggests the involvement of congenital CMV infection in a portion of children with ASD, although definite diagnosis was not obtained due to limited clinical data of the study subjects.